-
If (a + b) : √ab = 4 : 1, where a > b > 0, then a : b is
-
- (2 + √3) : (2 − √3)
- (2 − √3) : (2 + √3)
- (3 + √2) : (3 − √2)
- (3 − √2) : (3 + √2)
Correct Option: A
= | ⇒ | = | ||||
√ab | 1 | 2√ab | 1 |
By componendo and dividendo,
= | ||
a + b − 2 √ab | 1 |
⇒ | = | ||
(√a − √b)2 | (1)2 |
Again using componendo and dividendo,
= | ||
2√b | √ 3 − 1 |
⇒ | = | ||
√b | √ 3 − 1 |
On squaring both sides
= | ![]() | ![]() | 2 | = | |||
b | √ 3 − 1 | 3 + 1 − 2 √3 |
= | = | ||
4 − 2√3 | 2 − √3 |
2 + √3 : 2 − √3